TED Talks in EFL Context: An Alternative Way for Teaching and Improving Student’s Speaking Skills - Nursafira, Mutia Sari (Elsya : Journal of English Language Studies, 2020)
The technological advancement has made the media rapidly grow, particularly as a learning media. Teachers and educators today are required to be creative, innovative and updated in finding and using media as a learning tool in class. It can't be avoided anymore the use of technology in millennium era has become a necessity for teachers in EFL teaching. This study aims to discuss how a video-based conference video channel known as TED Talks can be useful in improving students’ speaking skills. The methodology used qualitative research and data collection obtained from relevant paper-based articles that have studied TED Talks as a learning medium to improve speaking skills. The results of this discussion paper showed that TED Talks has an effect on improving speaking among the EFL and also as a motivation for teachers and students to always keep spirit, inspirational and insightful. The novel finding of this study is that TED Talks also changes the students’ perspectives for the better, as they see that people from any country and ethnicity can speak English confidently in public.